A cointegration analysis on trade behaviour in selected ASEAN countries using dynamic OLS and Johansen Maximum Likelihood approaches - Abu Bakar, Nor'Aznin (Universiti Utara Malaysia, 2004)
This paper aims to analvse the trade behaviour of four selected ASEAN countries (based on their export/import products) by using a co-integration analysis. The demand for exports and imports are estimated for the period before the currency crisis erupted (1963-1995), using the dynamic OLS (DOLS) method. The Johansen Maximum Likelihood (JML) approach is also employed to compare the results obtained. The results show that foreign income has a significant impact on export demand, suggesting that foreign disturbance in the form of economic activities is likely to be transmitted to these countries. The Marshall Lemer conditions are easily met for the case of Malavsia and Thailand (DOLS and JML). For Indonesia and the Philippines, the sum of the price elasticities of exports and imports demands are less than unity, this can be explained by the J-curve, in which the currency depreciation will first worsen the trade balance before it improves and it takes time to affect the trade balance.